Women’s Empowerment: an Insight into History and the Present Day - Oksana Koshulko (SIASAT, 2021)
The article presents the results of research concerning the empowerment of women from the 17th to 21st century in various countries, including Mexico, the U.K., the U.S.A., Ukraine and France among others. Fourteen cases of women's empowerment in their areas of activity are explored, using case studies collected from primary and secondary data. Twelve of the cases are described and explored using secondary data and two cases using primary data, collected in 2019 in Kyiv, Ukraine. The cases are encrypted as Case 1 - C_ 1 through to Case 14 - C_ 14. The article is an important insight into women's empowerment through history to the present, showing how at times women have sacrificed themselves to achieve their aims and how these sacrifices are important for women of today. However, despite the achievements throughout the centuries, women must continue their struggle to obtain full rights and freedom for all women around the world.